A Phase I, Single-Ascending-Dose Study in Healthy Subjects to Assess the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of DS-2969b, a Novel GyrB Inhibitor - Dennie, Justin; Vandell, Alexander G; Inoue, Satoshi; Gajee, Roohi; Pav, Joseph; Zhang, George; Zamora, Cynthia; Masuda, Nobuhisa; Uchiyama, Minoru; Yamada, Makiko; Senaldi, Giorgio (Journal of clinical pharmacology, 2018)
DS-2969b is a novel GyrB inhibitor in development for the treatment of Clostridium difficile infection. The aim of this study was to assess the safety, tolerability, pharmacokinetics, and effects on normal gastrointestinal microbiota groups of single daily oral ascending doses of DS-2969b in healthy subjects. The study enrolled 6 sequential ascending dose cohorts (6 mg, 20 mg, 60 mg, 200 mg, 400 mg, and 600 mg). In each cohort, 6 subjects were administered DS-2969b and 2 subjects were administered matching placebo. DS-2969b was safe and well tolerated at all dose levels examined. All adverse events related to DS-2969b were mild to moderate in severity and predominantly related to the gastrointestinal tract. DS-2969a (free form of DS-2969b) plasma concentrations increased with increasing doses; however, both the maximum serum concentration and area under the plasma concentration-time curve generally increased less than dose proportionally. DS-2969a was predominantly eliminated in the urine, with feces as a minor route of elimination. While the overall proportion of DS-2969a eliminated in the feces was low, target fecal levels sufficient for C. difficile eradication were achieved within 24 hours of administration with doses of 60 mg or higher. In exploratory analyses, DS-2969b appeared to reduce bacterial counts in 8 of the 25 groups of normal intestinal microbiota examined, suggesting that DS-2969b has only a mild effect on intestinal microbiota. Data from this study support and encourage further development of DS-2969b as a novel treatment for C. difficile infection.